Estudo retrospectivo dos parâmetros de projeto e desempenho de tratores agrícolas - Herzog, Daniela (2024)
The agricultural tractor is considered one of the most important agricultural equipment and it is constantly undergoing transformation to improve the quality and performance of the agricultural operations carried out. Therefore, this work aimed to carry out a retrospective study of the main design and performance parameters used in the project of agricultural tractors. Thereby, a database was developed with information from 2.259 official test reports that follow Code 2 of the Organization for Economic Co-Operation and Development (OECD) and are available in global databases. In order to establish the different design and performance parameters used in the project of agricultural tractors, the tractor models present in the database were grouped and categorized according to the maximum engine power ranges. Thus, the attributes of agricultural tractors considered representative of their power classes were identified, regarding the performance characteristics of the engine, frame structure, transmission system, hydraulic system and drawbar performance. The results found demonstrate that as the power class of the agricultural tractors increases, the tractors become more efficient in terms of the performance of their engines and more technologically advanced, in addition to presenting design characteristics suitable for the specific functions to be performed. Furthermore, the results found indicate an increase in engine efficiency over the years, through a reduction in specific fuel consumption and an increase in power and torque. Finally, as the levels of restriction on emissions of polluting gases and particulate matter from agricultural tractor engines become more stringent, the exhaust gas treatment systems present in agricultural tractor engines are no longer used isolated but matching different exhaust gas treatment systems.